Analisis School Branding di YouTube LP Maarif Bangkit - Fitriyah, Siti Aminatul (LANCAH: Jurnal Inovasi dan Tren, 2024)
Education is one of the needs of every person. Education is also one of the determining aspects of national development progress. The fundamental goal of education is to improve a person's quality of life. This process is expected to help people master the purpose and meaning of life, and methods of carrying out responsibilities and living life efficiently. Competition in the learning area is unavoidable, and many educational institutions are carrying out mergers because customers are leaving these institutions. The educational institution in question is a madrasa. This school needs to be marketable so that it remains open. No matter how good a school is, if it is not promoted efficiently it will only affect a handful of students and will not be known by the public.